INVENTARISASI IKAN FAMILI CHAETODONTIDAE DI KAMPUNG TABLASUPA DAN KAMPUNG ENTIYEBO DISTRIK DEPAPRE KABUPATEN JAYAPURA - Leonardo Elisa Aisoi (NOVAE GUINEA Jurnal Biologi, 2015)
Research on Inventory Fish Chaetodontidae in Tablasupa Village and Entiyebo VillageDepapre District Jayapura Regency has implemented from March to June 2008. This study aims to determine the types of fish families Chaaetodontidae contained in coastal waters and the village of Kampung Tablasupa Entiyebo Depapre District Jayapura Regency and to determine the diversity of fish families Chetodontidae covering diversity, dominance types, kakayaan types, and community similarity. Research done by using the Line Transect method (Line Transect), with a length of 5000 cm transects each station (50 m). Data collection was performed by means of visual census transects at intervals corresponding to the left side and right side of the transect each 2.5 meters in doing after a quiet period, 20 minutes. Visual census results in the two villages namely Tablasupa Village on Alraikotu location, there are 18 types of the number 81 tails, while the location of Entiyebo Village Bitiyayu there are 12 types of the number 74 tails, of which 8 types contained in EntiyeboVillage also found in TablasupaVillage, so overall 21 species or 56.75% of the fish family Chaetodontidae in New Guinea. Fish species diversity index families in TablasupaVillage Chaetodontidae are 2,681 and 2,132 village Entiyebo is categorized being and dominance types in Tablasupa Village is 0.078 and the village of 0,564 Entiyebo categorized as low, whereas species richness in the village of TablasupaVillage are 0.222 and 0.162 Entiyebo is categorized Low and both areas have similarities of 0.533 or two areas are similar at 53% or 47%, while the rest are not similar.Â Keywords: Inventory, Fish family Chaetodontidae, Tablasupa Villageand EntiyeboVillage.